A wind resource assessment at Aħrax Point: A node for central Mediterranean offshore wind resource evaluation. Issue 5 (October 2016) - Farrugia, Robert N; Sant, Tonio
This article presents salient results from wind measurements conducted by the Malta Resources Authority at Aħrax Point on the Mediterranean island of Malta. The measurement exercise had the primary aim of enabling a better assessment of wind conditions in the near shore offshore environment, more specifically on an offshore reef known as Is-Sikka l-Bajda. The 80 metre wind monitoring mast installed at Aħrax Point generated data from various sensors at multiple monitoring levels and the analysis presented here divulges key parameters derived from this scientific study. The region lacks measured offshore wind data and the islands' position in the central Mediterranean makes such a data bank useful for offshore wind resource assessments, as well as for comparison with results generated by mesoscale meteorological models. This study investigates wind behaviour at Aħrax Point as a multi-level measurement node and the results are also compared to a re-analysis dataset in order to establish similarities or deviations of specific wind parameters.